Organizational Commitment, Management Accounting Information System Characteristics, and Managerial Performance: Evidence from Authorized Car Dealership Companies - Noor, Julfan Herliansyah; Agusty, Rizka Rahma (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2026)
This study examines the effect of organizational commitment and Management Accounting Information System (MAIS) characteristics on managerial performance in Authorized Car Dealership Companies. Managerial performance plays an important role in ensuring operational efficiency, business sustainability, and organizational competitiveness, particularly in companies operating in highly competitive sales and service environments. However, limited studies have specifically examined authorized car dealership companies, despite their unique operational complexity involving sales, service, spare parts management, customer relationship handling, and strict principal-dealer performance standards. This study addresses this gap by integrating organizational commitment and MAIS characteristics into a single empirical model within the automotive dealership sector. This study employed a quantitative approach using descriptive and verification methods. The total population consisted of 87 Authorized Car Dealership Companies, from which 42 companies were selected as research samples using probability sampling with a simple random sampling technique. Primary data were collected through questionnaires distributed to managerial-level respondents, while secondary data were obtained from company documents and relevant literature. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS version 4.0. The results show that organizational commitment has a significant positive effect on managerial performance. In addition, the characteristics of MAIS also have a significant positive effect on managerial performance. However, the normative commitment dimension, as well as the broad scope and aggregation dimensions of MAIS, have not yet reached optimal conditions and require further improvement. This study contributes to the literature by extending managerial performance research into the automotive dealership sector and provides practical implications for improving managerial effectiveness through stronger organizational commitment and better accounting information system quality